Intended Self-Presentation Tactics in Job Interviews: A 10-Country Study - Sandal, G.M.; van de Vijver, F.; Bye, H.H.; Sam, D.L.; Amponsah, B.; Cakar, N.; Franke, G.H.; Ismail, R.; Kjellsen, K.; Kosic, A.; Leontieva, A.; Mortazavi, S.; et al. (Journal of Cross-Cultural Psychology, 2014)
Intended self-presentation in job interviews was examined among university students in 10 countries (N = 3,509). The aim was to assess cross-cultural differences in the endorsement of self-presentation tactics, and whether such differences could be explained by cultural values and socioeconomic variables. The Cultural Impression Management Scale-Applicant Scale (CIM-A) was used that measures assertiveness, individual excellence, accommodation, and pointing out obstacles. Cross-cultural differences were found in endorsement of all tactics, most notably in individual excellence and pointing out obstacles. Importance assigned to self-presentation tactics was larger among individuals from cultures emphasizing embeddedness, mastery, and hierarchy, and with larger income disparities. The exception to this pattern was the American sample. Implications for personnel selection in international contexts are discussed. © The Author(s) 2014.
Keywords: affluence; cultural values; impression management; job interview; selection; self-presentation